Edukasi Peran Orang Tua Terhadap Anak Dalam Penggunaan Media Sosial Sebagai Bentuk Persiapan Menghadapi Revolusi Industri 5.0 - Sukrina Herman; Azhar Badriyyah (Puslitbang Akademi Relawan TIK Indonesia (ARTIKA), 2023)
Era of technological advancement, technical ideas can start from simple concepts and transform into large businesses that impact millions of people. This is different from the past when ideas only emerged in laboratories. Technological progress has infiltrated many aspects of human life, including education, sales, shopping, entertainment, and even media consumption. An illustrative example is the use of smartphones to access social networks, which can sometimes be challenging to control, especially among children today. The Community Service Program (PKM) aims to provide understanding, awareness, and education on the crucial role of parents in guiding children's use of social networks as preparation for the Industry 5.0 revolution. This initiative involves collaboration with village officials, community leaders, and digital experts. Using methods such as lectures, discussions, and Q&A sessions, the workshop utilizes presentations and video demonstrations to highlight AI threats. After the material presentation, interaction and prize distribution commend participation in the PKM. The research results indicate enthusiastic responses from the Kertajaya Village community, reflecting their willingness to actively monitor smartphone and social media usage in the future, especially concerning children. This reflects a promising step toward increased awareness and public education about the impact of technological advancements.